Pengaruh Lama Perendaman Ekstrak Biji Alpukat (Persea Americana) Terhadap Perubahan Warna Resin Akrilik (Kajian Pada Elemen Gigi Tiruan Akrilik) - Holie Fransiski; Nova Adrian (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: The denture element is the component that functions to chew food, besides the chewing function it also affects the aesthetics of a person. In the maintenance of denture hygiene, avocado extract can be an option because it has antibacterial and anti-fungal effects, it also has ingredients that can cause discolouration. Purpose: This study aims to determine the effect of soaking time in the avocado seed extract on the discolouration of the acrylic denture elements. Methods: The object of the study was an acrylic denture element with the Naperce brand with colour code A3. The research was conducted by immersing acrylic resin denture elements in aquadest and a solution of avocado seed extract. This study was divided into a treatment group and a control group. In each group 20 ml of fluid. First, the control group was the aqua dest group and the next for the avocado seed extract diet group. Colour measurement using a Spectrophotometry tool with the VITA easy shade V type after immersion at 30, and 45 minutes. The data calculation used the normality test with the Shapiro-Wilk method, the Mann-Whitney test, and the independent T-test. Results: The results obtained from this study showed no significant colour change (p> 0.05). Conclusion: The use of avocado seed extract as a denture-cleaning agent did not provide a significant discolouration of the acrylic denture elements.